Assessing the Vulnerability of a Coastal Community to Storm Surge: The Case of Barangay Baseco, City of Manila (Journal of Bangladesh Institute of Planners, 2018)
Disasters in the form of typhoon and storm surge-induced flooding can be very destructive for coastal communities. This study presents a quantitative framework for measuring the vulnerability of a coastal community in the City of Manila. The framework is adapted from the Vulnerability and Capacity Assessment (VCA) method presented by Prabhakar (2015), drawing on the Intergovernmental Panel on Climate Change (2007) concept of vulnerability. The study incorporates socio-economic factors and storm surge characteristics to ascertain the leading factors of vulnerability from a household perspective. Criteria were selected from different local and international methods used to assess climate change induced vulnerability of communities. Study findings draw on survey, key informant interview, estimation of spatial attributes and applicable published census data. The assessment results show that BASECO is highly vulnerable to storm surge impacts with an overall vulnerability score of 0.74 out of 1.00. While exposure is moderate with an index of 0.51 due to coastal flooding and extent of population exposed, sensitivity is high with 0.61 and adaptive capacity with 0.38 index value. This study suggests the updating of city’s land use plan and zoning policy based on hazard and risk information to guide medium term measures, such as relocation or settlement upgrading programs.JBIP, Vol. 11, 2018 (Printed in June 2020), pp. 107-123